Corrosion Characterisation of Al-Cu Reinforced In-Situ TiB2 - Rosmamuhamadani R. (MATEC Web of Conferences, 2016)
Aluminium (Al) based in-situ metal matrix composites (MMCs) have better properties and performance compared to ex-situ MMCs. In this research, aluminium-copper (Al-Cu) alloy was reinforced with 3 and 6wt.% titanium diboride (TiB2). Al-MMCs has been fabricated with salt route reaction process at 800 °C via potassium hexafluorotitanate (K2TiF6) and potassium tetrafluoroborate (KBF4) salts. Hardness vickers tester and Gamry-Electrod Potentiometer were used to characterize the hardness properties and to determine the corrosion rate of Al-Cu alloys. From results obtained, increased TiB2 contents will increase the hardness of Al-Cu alloys. Increased of TiB2 contents also will increase the corrosion rate of Al-Cu alloys. Al-Cu with 3wt.%TiB2 gave the good properties of corrosion when the wear rate recorded the lowest value compare to Al-Cu alloy itself and 6 wt.% TiB2. The corrosion rate of Al-Cu with 3wt.TiB2 was 16.15, while Al-Cu and Al-Cu-6wt%TiB2 were 22.5 and 58.7 mm/y respectively.